Popular Piety and the Muslim Middle Class Bourgeoisie in Indonesia - Alam, Lukis (Pascasarjana IAIN Pontianak, 2018)
This paper discusses the passion of Islamization of the New Order, at the same time the mainstream of this power is based on economic development that provides opportunities for the growth of the Muslim middle class. Patronage model used by the New Order gives an indication that the power built by this regime wants to instill a strong influence in society. At the same time, the New Order is depoliticizing the political attitudes of Muslims. This has implications for the marginalization of the interests of Muslims on the national stage. In this study will also be affirmed the influence of the New Order's power on the presence of the Muslim middle class. On the one hand their birth was the result of the economic development that the New Order echoed. On a different aspect, the presence of the middle class gives strong legitimacy that they are part of the dominating class structure in a country. Also will be reviewed about middle-class interference with the trend of Islamic populism that actually occurred in the era of the 80s, but re-spread after post-reform. Popular Islamic culture becomes a trend that spread through various media such as, internet, magazines, newspapers and so forth. This has received considerable response from middle-class Muslims and led to commodification. Religion facilitates to interact with modernity. Materialistic and hedonistic interests intersect with obedience in the practice of religion. On the one hand, the mode of consumption of the Muslim middle class changes with the adaptation of piety values in the public sphere.